Analisis Pembiayaan Akad Musyarakah pada Lembaga Keuangan Syari’ah di Indonesia: Studi Pendekatan NVivo dan Literatur Review - Maretha Ika Prajawati; Rohmadi; Doni Yusuf Bagaskara (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine financing analysis in sharia financial institutions in Indonesia using the NVivo approach. This research uses qualitative methodology with the Nvivo approach and literature review.